Strategies to Increase Financial Literacy for the People of Tirtawangunan Village - Febriansyah, Yudi; Dwi Martika, Lia; Fitriani, Chintia (EQUATOR SINAR AKADEMIA, 2024)
One of the problems faced by the community is financial management. Lack of knowledge about financial literacy can lead to various problems, such as difficulties in managing budgets, understanding investment concepts, managing debt, and planning for the financial future. To answer this, strategy training was carried out in improving financial literacy among the Tirtawangunan Village Community through community service activities with an assessment of success indicators and an evaluation of the results of the activity was carried out for 2 weeks after the activity took place. This is evident from the 25 trainees who have applied the use of financial record applications in managing finances more effectively and efficiently for those who are used as a strategy to improve financial literacy.